Management Advisory Services for Business Planning, Control and Decision - Harina, Ricardo M. (Mandaluyong City, Philippines : National Book Store, 2008)
It covered concepts and standards of management services practice by CPA's accounting; Financial management-related services; capital budgeting concepts and techniques; and project feasibility studies.
1. Management advisory services -- 2. Accounting systems -- 3. Management accounting -- 4. Financial statement analysis -- 5. Analysis of changes in sales, cost of sales and gross margin -- 6. Cost-volume profit analysis -- 7. Variable costing versus absorption costing -- 8. Activity based costing -- 9. Differential cost analysis -- 10. Pricing decision -- 11. Transfer pricing -- 12. Budgeting for profit and control -- 13. Standard costs and variance analysis -- 14. Quantitative methods for planning and control -- 15. Working capital management -- 16. Capital budgeting -- 17. Project feasibility study.
Keywords: ACCOUNTING -- PHILIPPINES